On isotactic polypropylene annealing: Difference in final properties of neat and β-nucleated polypropylene - Lenka Gajzlerova; Jana Navratilova; Sona Zenzingerova; David Jaska; Lubomir Benicek; Michal Kudlacek; Roman Cermak; Martin Obadal (eXPRESS Polymer Letters)
The effect of isotactic polypropylene (iPP) molecular weight and thermal treatment on final crystalline structure and mechanical properties were investigated by X-ray scattering, differential scanning calorimetry, tensile testing, and scanning electron microscopy. Neat and β-nucleated isotactic polypropylene were subjected to annealing above melting temperature of β-phase but still below melting temperature of α-phase, which caused both improvement of α crystallites and β to α-recrystallization, in case of nucleated material. As a consequence, the final mechanical properties like tensile strength and stiffness improved significantly. The increase is much more pronounced in the case of β to α-transformed materials with lower molecular weight. This phenomenon can also be attributed to the partial preservation of the specific structure of the amorphous phase present in β-nucleated polypropylene, in addition to the perfection of the crystalline phase. The amorphous phase comprises many interconnecting chains passing through several lamellae whereby providing a long-range effect.